Global projections of future cropland expansion to 2050 and direct impacts on biodiversity and carbon storage. (24th October 2018) - Molotoks, Amy; Stehfest, Elke; Doelman, Jonathan; Albanito, Fabrizio; Fitton, Nuala; Dawson, Terence P.; Smith, Pete
Abstract: Cropland expansion threatens biodiversity by driving habitat loss and impacts carbon storage through loss of biomass and soil carbon (C). There is a growing concern land‐use change (LUC) to cropland will result in a loss of ecosystem function and various ecosystem services essential for human health and well‐being. This paper examines projections of future cropland expansion from an integrated assessment model IMAGE 3.0 under a "business as usual" scenario and the direct impact on both biodiversity and C storage. By focusing on biodiversity hotspots and Alliance for Zero Extinction (AZE) sites, loss of habitat as well as potential impacts on endangered and critically endangered species are explored. With regards to C storage, the impact on both soil and vegetation standing C stocks are examined. We show that if projected trends are realized, there are likely to be severe consequences for these resources. Substantial loss of habitat in biodiversity hotspots such as Indo‐Burma, and the Philippians is expected as well as 50% of species in AZE sites losing part of their last remaining habitat. An estimated 13.7% of vegetation standing C stocks and 4.6% of soil C stocks are also projected to be lost in areas affected with Brazil and Mexico being identified as priorities in terms of both biodiversity and C losses from cropland expansion. Changes in policy to regulate projected cropland expansion, and increased measures to protect natural resources, are highly likely to be required to prevent these biodiversity and C losses in the future. Abstract : This article examines the projected impacts of cropland expansion on both carbon storage and biodiversity if current trends continue. It focuses on biodiversity hotspots and the Alliance for Zero Extinction (AZE) sites for biodiversity as well as both soil and standing vegetation carbon stocks. Results are compared on both a regional and national level identifying priority areas where impacts on both ecosystem services are likely to be the greatest.